Tyrannical power of the bishop and social space: The case of Mérida in the late 6th century - M. Yu. Birkin (Шаги, 2022)
The article focuses on the figure of an evil bishop in the “Lives of the Fathers of Merida” in the context of the image of a tyrant. The figures of the king and the bishop, on the one hand, and the tyrant and the bad bishop, on the other, are shown to be interconnected. The rhetoric associated with the image of a tyrant reflects the connection of the bad bishop to demonic forces, his fundamental alienness from the Christian community through being a member of corpus Antichristi. This results in his destroying the community (ciuitas) entrusted to him: it becomes subject to disturbances, famine, and disease. Ciuitas is understood as a sacralized social space, organized in accordance with the ideal divine order: Therefore, any action that profaned it was an act of tyranny. In turn, the true bishop set the unity of all elements of the Christian community, whose harmony and well-being depended on maintaining the order of the sacred. The key constituents of the ciuitas thus understood were churches and relics, the integration of which was ensured by the bishop. In the “Lives of the Fathers of Merida” attempts to seize these objects and attacks against the head of the community are depicted as the main tyrannical activities precisely because they disturb the functioning of the sacred space of the ciuitas.